THE CAUSES AND CONSEQUENCES OF THE POLITICS OF REGIONALISM IN INDIA - Nutan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper examines the causes and consequences of regionalism in India, exploring how it has influenced the political dynamics, governance, and national integration. The causes of regionalism are multifaceted, including historical, economic, linguistic, cultural, and political factors that have led to the emergence of regional identities and demands for autonomy. The paper also delves into the role of regional parties, the impact of economic disparities, and the implications of federalism in fueling regional aspirations. On the other hand, the consequences of regionalism are examined in terms of both positive and negative outcomes, such as the promotion of inclusive development and cultural preservation versus the challenges of fragmentation, secessionist movements, and threats to national unity. This study highlights the complex interplay between regionalism and Indian democracy, offering insights into its enduring impact on governance, policy-making, and national cohesion.